1990
DOI: 10.1172/jci114799
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 (IL-1) gene expression, synthesis, and effect of specific IL-1 receptor blockade in rabbit immune complex colitis.

Abstract: Interleukin I (IL-1) may be a key mediator of inflammation and tissue damage in inflammatory bowel disease (IBD). In rabbits with immune complex-induced colitis, IL-la and (3 mRNA levels were detectable at 4 h, peaked at 12 but were absent at 96 h after the induction of colitis. Colonic IL-1 tissue levels were measured by specific radioimmunoassays. IL-la was significantly elevated at 4 h (9.4±1.5 ng/g colon), progressively increased at 48 h (31±5.8 ng/g) and then decreased by 96 h (11.5±3.4 ng/g). IL-lft leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
1
5

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(135 citation statements)
references
References 61 publications
6
123
1
5
Order By: Relevance
“…The aim of this study was to determine whether inhibition of IL-1, as could be achieved by using a transgenic mouse that overexpressed the IL-1 receptor antagonist (IL-1ra), had an effect on SK pathogenesis. Such transgenic mice have been used in other inflammatory models and were shown to block IL-1 and diminish disease expression (15)(16)(17)(18). Our results with ocular infection with HSV demonstrate that IL-1ra transgenic (IL-1ra Tg) mice developed significantly milder disease and reduced corneal angiogenesis compared with IL-1ra Ϫ/Ϫ and C57BL/6 mice.…”
mentioning
confidence: 70%
“…The aim of this study was to determine whether inhibition of IL-1, as could be achieved by using a transgenic mouse that overexpressed the IL-1 receptor antagonist (IL-1ra), had an effect on SK pathogenesis. Such transgenic mice have been used in other inflammatory models and were shown to block IL-1 and diminish disease expression (15)(16)(17)(18). Our results with ocular infection with HSV demonstrate that IL-1ra transgenic (IL-1ra Tg) mice developed significantly milder disease and reduced corneal angiogenesis compared with IL-1ra Ϫ/Ϫ and C57BL/6 mice.…”
mentioning
confidence: 70%
“…The cytokines TNF-a and IL-1b play a pivotal role in pathogenesis of human and experimental colitis (42,43), and Abs against TNF-a are largely used in the clinical treatment of IBD (44). Previous reports have demonstrated that RvE1 treatment abolishes colonic mRNA expression of TNF-a and IL-1b in DSSand TNBS-induced colitis (7,25), which are associated with a dramatic inhibition of PMN infiltration of the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins encoded by the IL-1 a and IL-1/3 genes appear to play an important role in chronic IBD, since enhanced production of IL-1 has been reported in gut tissue of animal models of intestinal inflammation [13,14], as well as in the mucosa [15] and isolated cell preparations of patients with active IBD [16,17].…”
Section: Introductionmentioning
confidence: 99%